Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Which shows the correct simplification of [tex]7^8 \cdot 7^{-4}[/tex]?

A. [tex]7^8 \cdot 7^{-4} = 7^{8 \cdot (-4)} = 7^{-32}[/tex]
B. [tex]7^8 \cdot 7^{-4} = 7^{8 + (-4)} = 7^{-2}[/tex]
C. [tex]7^8 \cdot 7^{-4} = 7^{8 + (-4)} = 7^4[/tex]
D. [tex]7^8 \cdot 7^{-4} = 7^8 \cdot (-4) = 7^{12}[/tex]


Sagot :

Let's explore the multiplication of exponents with the same base to simplify the expression \( 7^8 \cdot 7^{-4} \).

When multiplying exponential expressions that have the same base, you add the exponents. This property can be expressed as:
[tex]\[ a^m \cdot a^n = a^{m+n} \][/tex]

Here, the base \( a \) is 7, \( m \) is 8, and \( n \) is -4.

Following the property, let's add the exponents:

[tex]\[ 7^8 \cdot 7^{-4} = 7^{8 + (-4)} \][/tex]

Perform the addition in the exponent:

[tex]\[ 8 + (-4) = 4 \][/tex]

Therefore, the expression simplifies to:

[tex]\[ 7^8 \cdot 7^{-4} = 7^4 \][/tex]

Among the given options, we find the correct simplification step-by-step:

[tex]\[ 7^8 \cdot 7^{-4}=7^{8+(-4)}=7^4 \][/tex]

Thus, the correct simplification is:
[tex]\[ 7^8 \cdot 7^{-4} = 7^4 \][/tex]

Additionally, let's calculate the final value of \( 7^4 \):

[tex]\[ 7^4 = 7 \times 7 \times 7 \times 7 = 2401 \][/tex]

So, the simplified exponent is \( 4 \) and the simplified result of the expression \( 7^4 \) is \( 2401 \). Overall, the correct answer is:

[tex]\[ 7^8 \cdot 7^{-4}=7^{8+(-4)}=7^4 \][/tex]